(untitled) - Chelang'a, James Kiprop (Advances in Social Sciences Research Journal, 2016)
Abstract Field courses are important areas for bridging lectures to practical lessons in every discipline learnt in colleges and universities. This paper assesses the perceptions of students on the administration and management of the field courses; the case of third year students at Moi university (Bachelor of Arts, PSA 312). It evaluates the administration and management of field courses at Moi University, and attempts to find solutions in relation to challenges therein. The study adopts a descriptive design, mixture of systematic and representative sampling techniques in its methodology. Generally, the study uses both qualitative and quantitative methods to access data, ultimately, the analysis was based on content, themes and output of SPSS information. A sample of 68 students was randomly chosen to participate in the study in 2015. The study findings highlight the imperatives of the need for policy in the administration and management of the field courses and makes recommendations, which Moi University and other institutions of higher learning can use to improve field course administration and management.